Cumulative health disadvantages: an empirical study of the health and mobility of the first cohort of migrant workers in China - Fengxian Qiu; Qingyang Kong; Dongjun Fan (Frontiers Media S.A., 2023)
BackgroundThe study aimed to understand the factors affecting the health and healthcare of the first cohort of migrant workers in China using the concept of the cumulative disadvantage framework.MethodsData from the China Migrants Dynamic Survey (2017) were used to analyze the process of cumulative disadvantage of health and healthcare among migrant workers. The study also analyzed the spatial lag problem between localized medical insurance policies and healthcare accessibility.ResultsThe results revealed a significant negative association between the mobility of the first cohort of migrant workers and their health status. Long-term exposure to hazardous work had a greater negative impact on their health. Chinese migrant workers faced significant obstacles in accessing healthcare due to the lack of portability in health insurance.ConclusionThe study emphasizes the urgent need for addressing the structural barriers hindering healthcare access and outcomes for migrant workers. It is crucial to promote a more equitable and sustainable healthcare system in China to ensure migrant workers' health and well-being.